Soil Nitrogen Transformation Process Influenced by Litterfall Manipulation in Two Subtropical Forest Types - Yan, Wende; Farooq, Taimoor Hassan; Chen, Yi; Wang, Wancai; Shabbir, Rubab; Kumar, Uttam; Riaz, Muhammad Umair; Alotaibi, Saqer S.; Peng, Yuanying; Chen, Xiaoyong (Frontiers in Plant Science, 2022)
Nitrogen (N) is often recognized as the primary limiting nutrient element for the growth and production of forests worldwide. Litterfall represents a significant pathway for returning nutrients from aboveground parts of trees to the soils and plays an essential role in N availability in different forest ecosystems. This study explores the N transformation processes under litterfall manipulation treatments in a Masson pine pure forest (MPPF), and Masson pine and Camphor tree mixed forest (MCMF) stands in subtropical southern China. The litterfall manipulation included litterfall addition (LA), litterfall removal (LR), and litterfall control (LC) treatments. The project aimed to examine how litterfall inputs affect the soil N process in different forest types in the study region. Results showed that soil ammonium N (NH4+-N) and nitrate N (NO3--N) content increased under LA treatment and decreased under LR treatment compared to LC treatment. LA treatment significantly increased soil total inorganic N (TIN) content by 41.86% and 22.19% in MPPF and MCMF, respectively. In contrast, LR treatment decreased the TIN content by 10% and 24% in MPPF and MCMF compared to LC treatment. Overall, the soil net ammonification, nitrification, and N mineralization rates were higher in MCMF than in MPPF; however, values in both forests were not significantly different. LA treatment significantly increased annual net ammonification, nitrification, and mineralization in both forest types (P < 0.05) compared to LC treatment. LR treatment significantly decreased the values (P < 0.05), except for ammonification, where LR treatment did not differ substantially compared to LC treatment. Our study suggested that changes in litterfall inputs would significantly alter soil N dynamics in forests in the study region. Moreover, mixed forest stands have higher nutrient returns due to mixed litter and higher decomposition compared to pure forest stands.